Influence of volume and thickness on shrinkage stress and depth of cure of conventional and bulk fill composites - Santin, Daniella Cristo (2019)
Objective: The present study investigated, in vitro, the influence of volume on shrinkage stress and the influence of thickness on the depth of cure by microhardness of convencional and bulk fill composite resins. Material and methods: Six commercial composite resins were selected: conventional (Filtek Z350 Z350; Vittra APS VAPS), high viscosity bulk fill (Filtek One Bulk Fill ONE; Opus Bulk Fill APS OBF) and low viscosity (Filtek Bulk Fill Flowable BFF; Opus Bulk Fill Flow APS OBFF). For the shrinkage stress analysis, specimens (n=5) were made varying the volume/C-factor (24 mm3/0.75 and 48 mm3/0.375). The contraction forces (N) generated from LED light-curing (30s; 1200mW/cm2) were recorded for 300s in an UTM and the shrinkage stress was calculated (MPa). For microhardness, using two molds with 4mm diameters, 2 and 4mm thicknesses (n=5), the specimens were made and light-cured for 30s. After 24h, Knoop microhardness measures (KHN) on the top and bottom surfaces were obtained and the ratio of bottom/top microhardness was calculated determining the depth of cure. After confirming normality (Shapiro-Wilk), all data were evaluated by two-way ANOVA, followed by Tukeys test (p<0.05). Results: The increase of composite resin volume resulted in higher shrinkage stress for the Z350, VAPS and ONE, regardless of the C-factor employed (p<0.05). The Z350, VAPS, BFF and OBF showed a decrease in microhardness (depth of cure) when the thickness was increased (p<0.05). Overall groups showed adequate polymerization (bottom/top microhardness >80%) at 2mm depth, except for the OBFF, while only the ONE presented adequate polymerization at 4mm depth. Conclusion: The volume and thickness of the increment influenced the stress and the depth of cure, respectively. The bulk fill ONE composite resin showed lower tension maintaining cure efficiency independent of volume compared to the other tested materials.